Shadowing: Warrants for Intersituational Variation in Ethnography. (August 2019) - Trouille, David; Tavory, Iddo
This article makes the case for shadowing as ethnographic methodology: focusing attention on what occurs as interlocutors move among settings and situations. Whereas ethnographers often zoom in on one principal set of situations or site, we argue that intersituational variation broadens and deepens the researcher's ethnographic account as well as affording important correctives to some common inferential pitfalls. We provide four warrants for shadowing: (a) buttressing intersituational claims, (b) deepening ethnographers' ability to trace meaning making by showing how meanings shift as they travel and how such shifts may affect interlocutors' understandings, (c) gaining leverage on the structure of subjects' social worlds, and (d) helping the ethnographer make larger causal arguments. We show the use value of these considerations through an analysis of violence and informal networks in an ethnography of immigrant Latinos who met to socialize and play soccer in a Los Angeles park.